Lean manufacturing, leadership and employees: the case of UAE SME manufacturing companies - Alefari, Mudhafar; Almanei, Mohammed; Salonitis, Konstantinos (Taylor & Francis, 2020)
Successful lean implementation to SMEs poses great challenges. Although lean principles, tools and strategies for implementation are widely known and well documented, companies still struggle. In the present paper, the challenges for the SMEs in their lean journey are discussed, focusing on leadership styles and their impact on how employees perform during the lean transition. The aim of the paper is to determine the extent to which the main principles of lean manufacturing are understood and adopted in manufacturing companies in a developing country such as the United Arabic Emirates (UAE) through a structured questionnaire. The degree of implementing lean manufacturing is assessed and discussed against literature review findings. Furthermore, the impact of various leadership styles during the lean transition is investigated. A second survey is used for capturing the current state with regards the employee performance and the role of leadership in manufacturing SMEs in the UAE.
Keywords: UAE; SME; lean leadership; lean implementation